Preparation of geometrically highly controlled Ga particle arrays on quasi-planar nanostructured surfaces as a SCALMS model system. Issue 6 (27th January 2023) - Hofer, André; Taccardi, Nicola; Moritz, Michael; Wichmann, Christoph; Hübner, Sabine; Drobek, Dominik; Engelhardt, Matthias; Papastavrou, Georg; Spiecker, Erdmann; Papp, Christian; Wasserscheid, Peter; Bachmann, Julien
Abstract : 2D SCALMS model system preparation offering a high degree of geometric control of the Ga matrix particles by combination of nanostructured surfaces with independent adjustment of the substrates' surface chemistry in a thermal decomposition approach. Abstract : This study establishes a preparative route towards a model system for supported catalytically active liquid metal solutions (SCALMS) on nanostructured substrates. This model is characterized by a uniquely precise geometrical control of the gallium particle size distribution. In a SCALMS system, the Ga serves as a matrix material which can be decorated with a catalytically active material subsequently. The corresponding Ga containing precursor is spin-coated on aluminum based substrates, previously nanostructured by electrochemical anodization. The highly ordered substrates are functionalized with distinct oxide coatings by atomic layer deposition (ALD) independently from the morphology. After preparation of the metal particles on the oxide interface, the characterization of our model system in terms of its geometry parameters (droplet diameter, size distribution and population density) points to SiO2 as the best suited surface for a highly controlled geometry. This flexible model system can be functionalized with a dissolved noble metal catalyst for the application chosen.